Can Loanwords Be Used to Date Biblical Texts, and If So, How? Linguistic and Philological Perspectives : Papers forming part of the 2017 and 2018 SBL Linguistics and Biblical Hebrew Seminar - Noonan, Benjamin J. 1981- (2020)
The question of whether or not biblical texts can be dated chronologically remains a lively topic of debate, and one important part of the conversation is the use of loanwords for dating biblical texts. This paper examines the philological relationship between lexical borrowings and the date of biblical texts. By focusing on the Hebrew Bible’s non-Semitic vocabulary, it argues that loanwords both cannot and can be used to date biblical traditions. Negatively, there is no clear one-to-one correspondence between a loanword of a given type and the date of a biblical text. Positively, loanwords can be useful for dating biblical texts in certain circumstances: first, the relative number and type of loanwords can point to plausible historical circumstances of borrowing, and second, phonological and morphological features can establish an approximate terminus ante quem for the borrowing.
Keywords: Biblical Hebrew; Biblical Aramaic; Philology; linguistic dating of biblical texts; language contact; loanwords